The Nucleus: An International Journal of Cytology and Allied Topics - a Bibliometric Study - Adithya Kumari, H.; Shivaram Rao, K. (Journal of Information and Knowledge, 2014)
Analyses articles published during 1992-95 in the journal ’The Nucleus: An International Journal of Cytology and Allied Topics’, to find the most frequently cited periodicals by the biological scientists in India. A list of 115 most commonly cited periodicals has been prepared. In addition to this, identifies the types of publication cited. Authorship pattern of contributions and countrywise distribution of frequently cited periodicals are also included.